Kepemimpinan kepala sekolah dalam meningkatkan mutu pendidikan di MITQ Jamilurrahman Yogyakarta - Widiyanto (At Turots: Jurnal Pendidikan Islam, 2023)
Many elementary schools, both public and private, are closed due to a shortage of students in various regions in Indonesia. But MITQ Jamilurrahman with a quota of 100 new students each year only takes one to four days to be fulfilled. This study aims to determine the leadership of school principals in improving the quality of education at MITQ Jamilurrahman Yogyakarta. This field research uses qualitative methods. Data collection uses triangulation techniques, namely interviews, observation and documentation. The results of this study inform that: 1) the leadership style of the MITQ Jamilurrahman principal is democratic-monarchical, this is evident in the way decisions are made by deliberation-consensus, 2) the principal's role is 2) the role of the principal includes several aspects that are carried out, namely as an educator, managers, administrators, supervisors, leaders, innovators, motivators and organizers. 3) school principals have carried out management fields, namely personnel management, curriculum management, student management, infrastructure management, financing management, and community relations management. Following up on these findings, following up on these findings, the management of the foundation as the organizing legal entity needs to provide regular and continuous guidance to all personnel, including school principals, teachers and staff through training, workshops and apprenticeships, additional facilities and infrastructure to improve the quality of education at MITQ Jamilurrahman.